2003
DOI: 10.1021/bc025638+
|View full text |Cite
|
Sign up to set email alerts
|

4-(2-Aminooxyethoxy)-2-(ethylureido)quinoline−Oligonucleotide Conjugates:  Synthesis, Binding Interactions, and Derivatization with Peptides

Abstract: Oligo-2'-O-methylribonucleotides conjugated with 4-(2-aminooxyethoxy)-2-(ethylureido)quinoline (AOQ) and 4-ethoxy-2-(ethylureido)quinoline (EOQ) were prepared by reaction of the AOQ or EOQ phosphoramidite with the protected oligonucleotide on a controlled pore glass support. Deprotection with ethylenediamine enabled successful isolation and purification of the highly reactive AOQ-conjugated oligomer. Polyacrylamide gel electrophoresis mobility shift experiments showed that the dissociation constants of complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…The resulting pentamer was found by HPLC analysis to be exactly the same as one produced with concentrated ammonia. This confirmed that ethylenediamine did not degrade the normal oligomers and that ethylenediamine can be safely used for cleavage and deprotection (27,28). …”
Section: Resultssupporting
confidence: 61%
“…The resulting pentamer was found by HPLC analysis to be exactly the same as one produced with concentrated ammonia. This confirmed that ethylenediamine did not degrade the normal oligomers and that ethylenediamine can be safely used for cleavage and deprotection (27,28). …”
Section: Resultssupporting
confidence: 61%
“…Oxime ligation is one of the most preferred procedures, due to the high chemoselectivity between an aminooxy function and a carbonyl group1, 2. Formation of chemoselective oxime bonds has been successfully applied for the synthesis of various peptide conjugates3, 4, glycopeptides5, conjugates of DNA with different biomolecules6, oligonucleotide–peptide conjugates7, 8, and proteins from peptide fragments9, 10. Moreover, oxime ligation has recently been investigated for the preparation of 18 F‐labeled peptide conjugates11, 12 and drug‐peptide conjugates13–15.…”
Section: Introductionmentioning
confidence: 99%
“…Our interest in the reactivity of this group is focused on the possibility of synthesizing polymer‐peptide conjugates. Through the linking groups introduced in the side chain or as end functionalization, the polymers can be coupled to peptides by means of standard amide coupling reactions or, alternatively, via chemoselective ligation with isothiocyanate groups to the corresponding thiourea 16,47–54…”
Section: Introductionmentioning
confidence: 99%